PENGARUH PERBANDINGAN JENIS PELARUT TERHADAP KANDUNGAN SENYAWA FENOL, a-TOKOFEROL, DAN KAROTENOID EKSTRAK Sargassum polycystum - Sri Yulianthi, Ni Nyoman; Suhendra, Lutfi; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 4 (2017): Desember, 2017)
Sargassum polycystum is one species of the brown algae class ( Phaeophyceae ). Brown algae that grows and spreads in almost all Indonesian sea, and has been known to contain various bioactive compounds that are useful in the health field. The objectives of this study were to determine the effect of solvent-type composition on the resulting would compound content of phenol, ?-tocopherol, and carotenoid extract of Sargassum polycystum , and to determine the ratio of solvent type that obtain the best of Sargassum polycystum extract. This experiment used a Randomized Block Design (RBD) with 7 treatment of ethanol and acetone (v/v) solvents, (0 : 10), (1 : 9), (3 : 7), (5 : 5), (7 : 3), (9 : 1),  (10 : 0). Furthermore, the treatment was grouped into 3 based on implementation time, so that obtained 21 units of experiments. The results showed that the ratio of solvent type was very significant (P<0,01) to all observed variables is rendement, total phenol, ?-tocopherol content, and total carotenoid. The effect treatment to the ratio of ethanol solvent : acetone (1: 9) v/v with 21.06 dielectric constant resulted in the best bioactive content of Sargassum polycystum extract with yield of 2,61%, total phenol 2,334  mgGAE/100g, ?-tocopherol 6,724 mg/100g, and total carotenoid 0,342%. Key words: Sargassum polycystum, bioactive compounds, ethanol, aceton, extraction .